Exploring the social representations of breastfeeding among mothers and grandmothers in Uruguay using word association - Alejandra Girona; Lucia de Pena; Hugo Cristo Sant’Anna; Gastón Ares; Rita Heck (International Breastfeeding Journal)
Abstract Background A comprehensive understanding of women lived experiences is crucial for developing effective strategies to support breastfeeding at both individual and systemic levels. In this context, this study aimed to explore the social representations of breastfeeding among Uruguayan mothers and grandmothers through a structural approach. Methods A total of 154 women, 77 mothers and 77 grandmothers, biologically related, were recruited from eight public health centers in Montevideo, Uruguay, between June and August 2022. Participants completed a free word association task using the stimuli “breastfeeding” and “exclusive breastfeeding.” Interviews were conducted by trained researchers via telephone, and participants were asked to provide 3–5 associations per term. Responses were analyzed using structural analysis with openEvoc software to identify core and peripheral elements of the social representations. Results “Love” emerged as the central element in the social representations of both breastfeeding and exclusive breastfeeding for mothers and grandmothers, highlighting the emotional and symbolic importance of breastfeeding across generations. Among mothers, representations were emotionally rich and experientially grounded, with frequent references to “baby,” “affection,” “attachment,” and health-related benefits. Mothers also acknowledged challenges such as “pain” and “tiredness.” In contrast, grandmothers’ representations were more heterogeneous and less detailed, especially for exclusive breastfeeding, which lacked a clear structure. Grandmothers frequently used normative or moral terms such as “correct,” “essential,” and “nutrition,” and showed limited familiarity with exclusive breastfeeding as a defined concept. Health-related benefits were present in peripheral areas for both groups, while references to the mother’s well-being were largely absent. Conclusions The findings highlight intergenerational continuity in the emotional anchoring of breastfeeding but reveal differences in knowledge and cognitive engagement, particularly concerning exclusive breastfeeding. While mothers integrate biomedical and experiential dimensions, grandmothers rely more on traditional values. These results underscore the need for generationally tailored communication strategies that acknowledge emotional and practical experiences and actively involve grandmothers in breastfeeding promotion efforts to strengthen intergenerational support for optimal breastfeeding practices.